An online credential repository for the Grid: MyProxy - Novotny, J.; Tuecke, S.; Welch, V. (Proceedings 10th IEEE International Symposium on High Performance Distributed Computing, 2001)
Grid portals, based on standard Web technologies, are increasingly used to provide user interfaces for computational and data grids. However, such Grid portals do not integrate cleanly with existing Grid security systems such as the Grid Security Infrastructure (GSI), due to lack of delegation capabilities in Web security mechanisms. We solve this problem using an online credentials repository system, called MyProxy. MyProxy allows Grid portals to use the GSI to interact with Grid resources in a standard, secure manner. We examine the requirements of Grid portals, give an overview of the GSI, and demonstrate how MyProxy enables them to function together. The architecture and security of the MyProxy system are described in detail.